Native conceptions of giftedness / by J. Karen Reynolds. - Reynolds, J. Karen (My University, 1992)
This study seeks to determine the relevance of "giftedness" in an isolated north-western Ontario Ojibway community and school. Specifically, Renzulli's (1986) model of "giftedness" is examined. This study begins with the community as the central element in its design. Qualitative research methods are used and include participant-observation, informally structured interviews, and document analysis. Elders, parents, teachers, and students, represent the participants. Data-collection took place during two, two-week visits to the site. Data analysis and interpretation was ongoing throughout the research process. The findings suggest that "giftedness" is a Euro- Western construct which is irrelevant and even in conflict with the norms of Sweetgrass community and school. This study does not recommend the use of the Renzulli (1986) model for "giftedness" in Sweetgrass, or in any focus for Native education which reflects the beliefs and perceptions of the participants in this community. Instead, culturally relevant enrichment strategies need to be developed and integrated throughout all aspects of curricula.
Keywords: Indians of North America Education.; Indians of North America Ontario, Northern.; Gifted children Education.